- Ultrasound in the emergency room in the diagnosis of jaundice - Clemente, Angel; Fernández, William; Popelka, Fernando (Cirugía del Uruguay, 1993)
The authors analyse a series of 100 echographic studies carried out as urgencies with portable units in patients that consulted the Emergency Department because of jaundice, with other clinica/ signs that suggested surgical etiology.